Aspirations and investments in livestock: Evidence of an aspiration failure in Kenya - Tabe-Ojong, Martin Paul Jr.; Heckelei, Thomas; Rasch, Sebastian (Agricultural and Applied Economics Association, 2022)
Aspirations have been shown to positively influence future-oriented behavior and ensuing outcomes. But they may also fail to do so when the aspired-to-status is too far away from the current one. Theoretical predictions suggest an inverted U-shaped relationship between this aspiration gap and the effort to achieve what is aspired to. Aspirations that are ahead but not too far ahead of the current status serve as the best incentives for investments. We examine the income aspiration gap of smallholder households and relate it to livestock in a pastoral setting in Northern Kenya. Our focus on livestock is guided by the burgeoning recognition of livestock as an investment and saving conduit for many households in pastoral communities in developing nations. Employing different empirical strategies including parametric and semiparametric techniques, we find livestock to be increasing with aspirations up to a threshold, from which it then declines leading to an aspiration failure. Different U-shaped tests confirm this relationship, bolstering the evidence of an aspiration failure. To unpack which livestock matters more relative to the others, we perform some heterogeneity analysis and found cattle to respond most to the aspiration gap. The findings are robust to the inclusion of relevant controls, truncations at zero and different variable transformations. We also show that the findings are unlikely to be driven by unobserved heterogeneity. A dive into mechanisms reveals that the internal locus of control, i.e. the degree to which individuals believe they control outcomes in their lives, decreases with the aspiration gap. Our findings have two implications: first, it reinforces previous claims of the role of psychological constraints on poverty reduction and rural development. More importantly, it has implications for the current debates and plans for boosting the development of the livestock sector in Africa as a pathway to overall economic development.